2021
DOI: 10.3390/molecules26040878
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Effects of Chemical Chaperone—TUDCA on ER-Stressed NHAC-kn Human Articular Chondrocytes Cultured in Normoxic and Hypoxic Conditions

Abstract: Osteoarthritis (OA) is considered one of the most common arthritic diseases characterized by progressive degradation and abnormal remodeling of articular cartilage. Potential therapeutics for OA aim at restoring proper chondrocyte functioning and inhibiting apoptosis. Previous studies have demonstrated that tauroursodeoxycholic acid (TUDCA) showed anti-inflammatory and anti-apoptotic activity in many models of various diseases, acting mainly via alleviation of endoplasmic reticulum (ER) stress. However, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…found that ursodeoxycholic acid, a hydrophilic bile acid, which has antioxidant and anti‐inflammatory activities, could induce bone regeneration via stimulating the osteogenic differentiation of MSCs 22 . Additionally, tauroursodeoxycholic acid was identified as a potential candidate for osteoarthritis by its chondroprotective 23,24 . In this study, we found a small molecular compound of bile acid family, NAT, which could enhance expression of COL2A1 and OCN both in vivo and in vitro , ameliorate the secondary osteoporosis, and delay the development of IDD.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…found that ursodeoxycholic acid, a hydrophilic bile acid, which has antioxidant and anti‐inflammatory activities, could induce bone regeneration via stimulating the osteogenic differentiation of MSCs 22 . Additionally, tauroursodeoxycholic acid was identified as a potential candidate for osteoarthritis by its chondroprotective 23,24 . In this study, we found a small molecular compound of bile acid family, NAT, which could enhance expression of COL2A1 and OCN both in vivo and in vitro , ameliorate the secondary osteoporosis, and delay the development of IDD.…”
Section: Discussionmentioning
confidence: 74%
“…22 Additionally, tauroursodeoxycholic acid was identified as a potential candidate for osteoarthritis by its chondroprotective. 23,24 In this study, we found a small molecular compound of bile acid family, NAT, which could enhance expression of COL2A1 and OCN both in vivo and in vitro, ameliorate the secondary osteoporosis, and delay the development of IDD. Moreover, we confirmed that a low dose of NAT showed major impact on osteoblasts differentiation.…”
Section: Main Findings Of This Studymentioning
confidence: 83%
“…Meanwhile, it is widely accepted that ER stress is directly associated with chondrocytes apoptosis and death [38][39][40] . What's more, recent studies confirmed OA inflammation is also related to ER stress [41][42][43][44][45] . Be similar with these obtained conclusions, we found by directly bound with IRE1α, SA inhibited IRE1α mediated ER stress and subsequently promotes chondrocytes proliferation, decreases inflammatory factors expression and inhibits chondrocytes apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…It is widely accepted that ER stress is directly associated with chondrocyte apoptosis and death [48][49][50] . Moreover, recent studies have confirmed that OA inflammation is related to ER stress [51][52][53][54][55] . In this study, we first detected the expression levels of PERK, p-PERK, IRE1α, p-IRE1α, and AFT6 after stimulation with TNF-α in the presence of SA and found that SA did not influence TNF-α-induced PERK phosphorylation or ATF6 expression.…”
Section: Discussionmentioning
confidence: 89%